Penentuan Koefisien Reaerasi Sungai Bedadung Hilir Metode Perubahan Defisit Oksigen (Studi Kasus di Kecamatan Balung, Jember) - Wahyuningsih, Sri; Dharmawan, Agus; Imamah, Imamah (Universitas Diponegoro, 2020)
Dissolved Oxygen (DO) is one of the most important parameters reflecting the ecological health of the river. DO supply must be maintained to support the life of aquatic organisms. DO supply obtained by oxygen transfer from the atmosphere to water. This research aimed to determine reaeration (continuous addition of oxygen) coefficients (KR) of Bedadung Downstream using the exchange of DO deficit. This approach uses the rate of mass transfer of oxygen from the air to the river water. The raw data was obtained by measuring stream-flow, temperature, and DO at three observed stations segment Balung district, Jember. The result showed the values of the reaeration coefficient (3 stations) were 36,084, 47,397, and 83,114 /day sequentially and tended to line up. The amount of KR obtained from the oxygen deficit and travel time of river water. The average KR was 55.532/day. High KR values indicate the ability of rivers that can supply oxygen naturally.